2011
DOI: 10.1007/s00267-011-9704-6
|View full text |Cite
|
Sign up to set email alerts
|

Outreach Programs, Peer Pressure, and Common Sense: What Motivates Homeowners to Mitigate Wildfire Risk?

Abstract: In recent years, altered forest conditions, climate change, and the increasing numbers of homes built in fire prone areas has meant that wildfires are affecting more people. An important part of minimizing the potential negative impacts of wildfire is engaging homeowners in mitigating the fire hazard on their land. It is therefore important to understand what makes homeowners more or less willing to take action. The research presented here comes from a study that interviewed a total of 198 homeowners in six co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
49
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 15 publications
6
49
0
Order By: Relevance
“…These factors were not unique to recreational property owners in Jasper National Park; they were consistent across other sites that included permanent residents in non-protected areas in the USA and Australia. Although McCaffrey et al (2011) found that part-time residency was a reason for not taking wildfire mitigation action they also noted no obvious differences in mitigation actions between part-time and full-time residents.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…These factors were not unique to recreational property owners in Jasper National Park; they were consistent across other sites that included permanent residents in non-protected areas in the USA and Australia. Although McCaffrey et al (2011) found that part-time residency was a reason for not taking wildfire mitigation action they also noted no obvious differences in mitigation actions between part-time and full-time residents.…”
Section: Introductionmentioning
confidence: 95%
“…The influence of perceived risk on wildfire mitigation among homeowners varies considerably (McGee 2005, Collins 2009, McFarlane et al 2011. Among the factors that contribute to variation in risk judgements and subsequent mitigation action are the subjective nature of perceived risk, the spatial scale and time frame of the assessment, and attention to what is at risk (McCaffrey 2008). Other perceptions may be more important than perceived risk.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations